2016
DOI: 10.1111/ejh.12728
|View full text |Cite
|
Sign up to set email alerts
|

Smoldering multiple myeloma risk factors for progression: a Danish population‐based cohort study

Abstract: Several risk scores for disease progression in patients with smoldering multiple myeloma (SMM) have been proposed; however, all have been developed using single-center registries. To examine risk factors for time to progression (TTP) to multiple myeloma (MM) for SMM, we analyzed a nationwide population-based cohort of 321 patients with newly diagnosed SMM registered within the Danish Multiple Myeloma Registry between 2005 and 2014. Significant univariable risk factors for TTP were selected for multivariable Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 18 publications
0
40
0
2
Order By: Relevance
“…Complete follow‐up was available for all but one patient (n = 2557). The registry contains information on baseline biochemistry, treatment regimens, and response to treatment as described previously . Cyclophosphamide‐dexamethasone (CyDex)‐based induction regimens were mainly used in the calendar period 2005‐2008 before ASCT, and this regime was in the calendar period 2009‐2013 changed to bortezomib‐dexamethasone (VD)‐based induction regimens alone or in combination with cyclophosphamide (VCD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complete follow‐up was available for all but one patient (n = 2557). The registry contains information on baseline biochemistry, treatment regimens, and response to treatment as described previously . Cyclophosphamide‐dexamethasone (CyDex)‐based induction regimens were mainly used in the calendar period 2005‐2008 before ASCT, and this regime was in the calendar period 2009‐2013 changed to bortezomib‐dexamethasone (VD)‐based induction regimens alone or in combination with cyclophosphamide (VCD).…”
Section: Methodsmentioning
confidence: 99%
“…The registry contains information on baseline biochemistry, treatment regimens, and response to treatment as described previously. 22 Immunoglobulin substitution therapy, pneumococcal vaccination, or antibiotic prophylaxis were not routinely used for Danish MM patients during the study period. 23 Qualitative immunoparesis was defined as one or more of uninvolved immunoglobulins below the normal levels IgG <6.1 g/L, IgA <0.70 g/L and/or IgM <0.39 g/L at time of diagnosis.…”
Section: Study Populationmentioning
confidence: 99%
“…Serum free light chain (FLC) levels and FLC ratio were not available in all patients and consequently we did not find a statistically significant relationship with progression. However, two recent studies (Waxman et al , ; Sorrig et al , ) observed that an abnormal FLC ratio is not considerable as a stand‐alone high risk factor for progression to active MM in SMM patients.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Treatment should be considered in these patients to prevent serious end-organ damage such as bone fractures or renal failure, which can have longterm effects on the quality of life of patients. However, two recent studies showed that SMM patients with a FLC ratio ≥100 have a 2-year progression risk of 30% and 64% [19,20], which is lower than reported in two previous studies (progression risk at 2 years:~80%) [21,22] that were used for these updated IMWG criteria [18]. The authors from these studies conclude that FLC ratio ≥100 as a sole criterion for treating as active MM may not be justified, but that very close monitoring is warranted for this group.…”
Section: Smoldering Multiple Myelomamentioning
confidence: 99%
“…Several other prognostic models have been published, including a recent Danish model derived from a population-based study, in which M-protein ≥30 g/ L and immunoparesis were markers for time to progression to MM in SMM (Table 3) [20]. In addition, the Arkansas group generated a risk-stratification model based on expression levels of only four genes combined with serum M-protein (≥30 g/L) and albumin levels (<35 g/L).…”
Section: Prediction Models In Smmmentioning
confidence: 99%